Pengembangan Kurikulum PAI Berbasis Kearifan Lokal - Husni, Husni (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2024)
This research aims to develop an Islamic Religious Education (PAI) curriculum that integrates local wisdom values ​​to enrich students' learning experiences and support the development of their character and competencies. This research uses a library research approach to develop an Islamic Religious Education (PAI) curriculum based on local wisdom, by collecting and analyzing information from related books and scientific journals. Data collection techniques include identification, collection, classification and content analysis of relevant literature. The collected data was then analyzed descriptively to describe the concept of local wisdom, principles of curriculum development, and examples of implementing PAI based on local wisdom. The results of this analysis are synthesized to form a conceptual framework and produce practical recommendations for relevant curriculum development. The result of this work, namely the development of an Islamic Religious Education (PAI) curriculum based on local wisdom, is a complex effort involving analysis of local needs, intensive training for teachers, as well as the development of relevant and contextual teaching materials. By utilizing interactive learning strategies and collaboration with local communities, this curriculum becomes more relevant and meaningful for students, helping them understand local religious and cultural values. Regular evaluations ensure the effectiveness of the integration of local wisdom, while strong collaboration with community leaders and parents strengthens the relationship between the school and the community. The implication of this effort is to create more meaningful learning, increase students' understanding of religious and cultural values, and empower teachers to create a dynamic and inspiring learning environment.